Recombinant EGFL7 Mitigated Pressure Overload-Induced Cardiac Remodeling by Blocking PI3Kγ/AKT/NFκB Signaling in Macrophages - Li, Lei; Zhao, Ying; Hu, Ying; Wang, Xiaohui; Jin, Qun; Zhao, Ying (Frontiers in Pharmacology, 2022)
Inflammation and endothelial dysfunction play an important role in heart failure (HF). Epidermal growth factor-like protein 7 (EGFL7) is upregulated during pathological hypoxia and exerts a protective role. However, it is unclear whether there is a link between abnormal EGFL7 expression and inflammation in overload stress-induced heart failure. Our results showed that EGFL7 transiently increased during the early hypertrophic stage and in hypertensive patients without heart failure. However, it decreased to the basal line in the heart tissue 8 weeks post-transverse aortic constriction (TAC) or hypertensive patients with heart failure. Knockdown of EGFL7 with siRNA in vivo accelerated cardiac dysfunction, fibrosis, and macrophage infiltration 4 weeks after TAC. Deletion of macrophages in siR-EGFL7-TAC mice rescued that pathological phenotype. In vitro research revealed the mechanism. PI3Kγ/AKT/NFκB signaling in macrophages was activated by the supernatant from endothelial cells stimulated by siR-EGFL7+phenylephrine. More macrophages adhered to endothelial cells, but pretreatment of macrophages with PI3Kγ inhibitors decreased the adhesion of macrophages to endothelial cells. Ultimately, treatment with recombinant rmEGFL7 rescued cardiac dysfunction and macrophage infiltration in siR-EGFL7-TAC mice. In conclusion, EGFL7 is a potential inhibitor of macrophage adhesion to mouse aortic endothelial cells. The downregulation of EGFL7 combined with increased macrophage infiltration further promoted cardiac dysfunction under pressure overload stress. Mechanistically, EGFL7 reduced endothelial cell adhesion molecule expression and inhibited the PI3Kγ/AKT/NFκB signaling pathway in macrophages.